Beljakovine, esencialno hranilo za človeka. Kdaj, kaj in koliko? - Podlogar, Tim (Šport (Ljubljana), 2017)
Proteins play a very important role in humans, especially in athletes given that proteins are the building blocks of muscles. Proteins consist of different amino acids, of which 9 are called essential and humans need to consume them with a diet. Amino acid leucine appears to play a crucial role in muscle protein synthesis because of its ability to activate mTOR pathway, which in turn initiates muscle protein synthesis. This article presents current evidence about the quality, quantity and timing of protein intake and health consequences of increased protein intake. At the end of article guidelines for protein intake for general public, athletes and elderly are presented.
Keywords: beljakovine; leucine; levcin; mišična masa; proteins; sport; sports nutrition; šport; športna prehrana